Physicaland mechanical behavior of concrete in seawater under high hydrostatic pressure - Md. S., Islam; Kaushik, S. K.; Md. M., Islam (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/